Stress distribution in an infinite elastic body containing two neighboring locally curved fibers - Kosker, R.; Cinar, N. T. (SPRINGER, 2009)
A method is developed for analyzing the stresses in an infinite elastic body containing two neighboring inphase locally curved fibers located along two parallel lines. The body is loaded at infinity by uniformly distributed nor mal forces in the direction of fibers. The investigation is carried out within the frame work of a piecewise homogeneous body model with the use of the three-dimensional ex act equations of the elasticity theory. Numerical results for stress distributions in the body and for the influence of interaction between fibers on these distributions are given.
Keywords: composite; fibers; stress distribution; local curving; Mechanics; Materials Science; Polymer Science